HIV Proteins and Endothelial Dysfunction: Implications in Cardiovascular Disease - Anand, Appakkudal R.; Rachel, Gladys; Parthasarathy, Durgadevi (Frontiers in Cardiovascular Medicine, 2018)
With the success of antiretroviral therapy (ART), a dramatic decrease in viral burden and opportunistic infections and an increase in life expectancy has been observed in human immunodeficiency virus (HIV) infected individuals. However, it is now clear that HIV- infected individuals have enhanced susceptibility to non-AIDS (Acquired immunodeficiency syndrome)-related complications such as cardiovascular disease (CVD). CVDs such as atherosclerosis have become a significant cause of morbidity and mortality in individuals with HIV infection. Though studies indicate that ART itself may increase the risk to develop CVD, recent studies suggest a more important role for HIV infection in contributing to CVD independently of the traditional risk factors. Endothelial dysfunction triggered by HIV infection has been identified as a critical link between infection, inflammation/immune activation, and atherosclerosis. Considering the inability of HIV to actively replicate in endothelial cells, endothelial dysfunction depends on both HIV-encoded proteins as well as inflammatory mediators released in the microenvironment by HIV-infected cells. Indeed, the HIV proteins, gp120 (envelope glycoprotein) and Tat (transactivator of viral replication), are actively secreted into the endothelial cell micro-environment during HIV infection, while Nef can be actively transferred onto endothelial cells during HIV infection. These proteins can have significant direct effects on the endothelium. These include a range of responses that contribute to endothelial dysfunction, including enhanced adhesiveness, permeability, cell proliferation, apoptosis, oxidative stress as well as activation of cytokine secretion. This review summarizes the current understanding of the interactions of HIV, specifically its proteins with endothelial cells and its implications in cardiovascular disease. We analyze recent in vitro and in vivo studies examining endothelial dysfunction in response to HIV proteins. Furthermore, we discuss the multiple mechanisms by which these viral proteins damage the vascular endothelium in HIV patients. A better understanding of the molecular mechanisms of HIV protein associated endothelial dysfunction leading to cardiovascular disease is likely to be pivotal in devising new strategies to treat and prevent cardiovascular disease in HIV-infected patients.